1998
DOI: 10.1103/physrevb.57.7653
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of isomorphous models of alloys

Abstract: Order-N methods for calculating the electronic structure of clusters containing hundreds of atoms using realistic self-consistent density-functional theory local-density approximation potentials make it possible to test alloy theories more definitively. Tests are carried out on isomorphous models of alloys in which the atoms of each species are treated as identical. In contrast, the order-N calculations lead to a polymorphous model in which all of the atoms are unique. Isomorphous models are seen to reproduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 41 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…84 As one can see from Fig. 5, the separation between the Cu and Zn d bands is of the order of the bandwidth and this is a case where a comparison between the CPA and the ''exact'' re- sults for the simple analytical models shows large discrepancies.…”
Section: A Density Of States For a Completely Random Alloymentioning
confidence: 96%
“…84 As one can see from Fig. 5, the separation between the Cu and Zn d bands is of the order of the bandwidth and this is a case where a comparison between the CPA and the ''exact'' re- sults for the simple analytical models shows large discrepancies.…”
Section: A Density Of States For a Completely Random Alloymentioning
confidence: 96%
“…This failure has stimulated many authors that envisaged CPA generalizations aimed to include the effects of different chemical environments. [42][43][44][45][46] In this paper, we define a class of approximations for DFT-based electronic theories in which most of the above CPA generalizations can be included. We shall refer to the approximations belonging to such a class as GCPA.…”
Section: A Generalized Coherent-potential Approximations For the Scamentioning
confidence: 99%
“…In the LSGF approach all the atoms in the supercell are different due to their different local environment while in the usual SS-DFT-CPA approach one deals only with average quantities, i.e., in terminology of the Ref. [35], the LSGF supercell approach is equivalent to the polymorphous model of the alloy while the effective-medium approach is equivalent to the isomorphous model. However, it is obvious, that this can be done on average.…”
Section: Net Charge and Madelung Potential In Metallic Alloysmentioning
confidence: 99%
“…Based on the fact, that a single impurity in a metallic host is a particular case of a dilute random alloy, one would expect, and the results for a single Cu impurity in Pt presented in the previous section unambiguously indicate this, that the screening effects in the two cases are similar. It is therefore surprising that Faulkner et al [35] and Ujfalussy et al [22] claim that the screening in a random alloy is qualitatively different from that found in a single impurity system. In fact, these authors found extremely long-range correlations between the Madelung potential at some particular site and the net charges at the other sites.…”
Section: Screening Charge In Metallic Alloysmentioning
confidence: 99%